POSSIBILITIES OF COLOR DUPLEX IMAGING IN THE DIAGNOSIS OF OCULAR VASCULAR PATHOLOGY - T. N. Kiseleva; M. S. Zaitsev; K. A. Ramazanova; K. V. Lugovkina (Российский офтальмологический журнал, 2018)
The literary review presents the results of domestic and foreign studies of blood flow in the arteries and veins of the eye and orbit using color Doppler Imaging (CDI) and pulsed dopplerography. These methods are used to obtain the data on linear blood flow velocity and vascular resistance in different areas of the ocular vascular system and detect the correlation thereof with the severity of vascular disorders. CDI demonstrates the possibilities of multiple application in order to obtain reliable results in the diagnosis and evaluation of the effectiveness of treatment of the vascular pathology of the eye. For citation: Kiseleva T.N., Zaitsev M.S., Ramazanova K.A., Lugovkina K.V. Possibilities of color Duplex Imaging in the diagnosis of ocular vascular pathology. Russian ophthalmological journal. 2018; 11 (3): 84-94 (In Russian). doi: 10.21516/2072-0076-2018-11-3-84-94